(untitled) (Al Dzahab, 2025)
Purpose: This study aims to identify and analyze the factors influencing the behavior of Generation Z Muslim consumers in using sharia e-commerce in Indonesia amid the rapid development of digital technology and the increasing integration of Islamic principles in digital trading platforms. Design/methodology/approach: This study employs a literature review method by examining various scientific articles, academic journals, and other relevant references related to consumer behavior, sharia e-commerce, religiosity, and digital technology. The collected data were analyzed qualitatively using a descriptive-analytical approach to synthesize findings from previous studies and conceptual discussions. Findings: The results indicate that the behavior of Generation Z Muslim consumers in utilizing sharia e-commerce is influenced by several key factors, including the convenience and accessibility of digital transactions, perceived usefulness and ease of use of the system, the influence of social media and digital influencers, awareness of product halalness, and the level of individual religiosity. In addition, psychological and social aspects such as digital lifestyle, self-identity, and the fear of missing out (FOMO) phenomenon also play an important role in shaping purchasing decisions on sharia-based digital platforms. Research implications: The findings suggest that the development of sharia e-commerce platforms should integrate technological innovation with the consistent implementation of sharia principles to strengthen trust and loyalty among Generation Z Muslim consumers. This integration is also expected to support the development of an ethical, inclusive, and sustainable digital economic ecosystem in Indonesia. Keywords: Generation Z; Consumer Behavior; E-Commerce